Trauma Patient Care at the Scene and During Transportation by Emergency Medical Technician Personnel - Awae, Hisham; Daemayu, Amanee (Princess of Naradhiwas University Journal, 2021)
Emergency injury is a life-threatening condition. It can happen at any time and can happen to any age. This resulted in massive loss of life and disability. Currently, the trauma patient care system has become more advanced. In each area, emergency operations teams have been developed to provide assistance at the scene of incidents and during transfer in accordance with the area of assistance aiming to provide trauma patient access to timely medical care. The emergency medical technician personnel are considered to be key personnel in emergency operations and to be a person in an area near the scene with specialized knowledge and skills in emergency injury assessment. In addition, the emergency medical technician personnel can provide primary care at the scene and during transfer to a medical facility located in a remote area continuously, appropriately, and efficiently for trauma patients. Resulting in reduced the lass of mortality, disability proportionally and health care costs of health care system. The review of emergency operations data found that basic emergency operations, which consist of emergency medical technician personnel as the number of operations, have increased and emergency medical technician personnel in basic life support unit are considered as significant people in helping the trauma patients. The author will explain the roles of emergency medical technician personnel in trauma patient care at the scene and during transfer in four areas as follows: (1) Emergency notification from the Command Center 1669, (2) Assessment and care for accident victims at the accident scenes, (3) Resuscitation for accident victims that have experienced cardiac arrest at the scene of emergency accidents and (4) the transport and care during transfer. The findings can be used as guidelines for emergency medical technician personnel to apply in appropriate contexts of work in the future.